Attributes of Mobile Technology Adoption Acceptance from Users Perspective - Md Yassin, Azlina; Al Naqbi, Saeed (International Journal of Sustainable Construction Engineering and Technology, 2022)
The most significant challenge associated with the operationalization of user-based technology emerged as technology acceptance among the public. This study aims to investigate the challenges in mobile technology adoption in the Abu Dhabi Emirate by identifying 52 factors that motivate users to adopt mobile technology across a broad spectrum. These factors were clustered into six categories namely Perceived Ease of Use (PEOU) User Experience (UE) Attitude (ATT), Customer Satisfaction Excellence (CSE) Perceived Usefulness (PU) and Intention to Use (INU). The data was collected through 396 questionnaires to gauge the perception of the public. The data was analysed statistically and found that all of the categories have Cronbach Alpha values greater than 0.7 which indicate that the data was reliable and consistent. The data was also assessed for its normality and found that the skewness and kurtosis values were in the range of normal distribution. For ranking analysis, it was found that the three most common categories considered by respondents when using any technology is Perceived Ease of Use. User experience is the second most important driving respondents' use of technology. This is followed by the user's attitude, which is what drives the adoption of any technology. This findings help the new technology providers to understand the acceptance patterns of the users.